RELATIONSHIP BETWEEN ORGANIZATIONAL AND MANAGERIAL FACTORS, AND THE HUMAN RESOURCE PLANNING’S EFFECTIVENESS. EVIDENCE FROM MALAYSIA PUBLIC SERVICES AGENCIES - Sopian, Bujang; Ahmad Sofian, Shminan (2010)
The purpose of this study is to investigate the relationship between organizational and managerial factors namely autonomy, internal and external support, and integration human resource planning (HRP) effectiveness of Malaysia Public Service Agencies. As HRP is about a process of obtaining the right number and kind of people at the right time in order to fulfill organizational needs, therefore is importance to ensure that this right number of people should be doing the right type of work at the right time and place to produced desirable result. Thus, HRP is the decision making and action process in determining how many people needed and where or how to acquire them. In this study the data were collected from 44 top management individuals representing 41 government agencies. The result of the correlation analysis shows that there are two independent variables i.e. integration and external support have a significant positive correlation with HRP effectiveness in the organizations studied. Furthermore, a Multiple Regression analysis conducted found that the proposed model was accepted i.e. all organizational and managerial factors does influence HRP effectiveness of organizations. Moreover, the integration – the integration of agencies HRP and strategic planning or organization was found significantly contribute to the HRP effectiveness of the organization.